A New Species of Aspidistra (Asparagaceae) from Guizhou, China - Sun, Qing-Wen; Xu, Wen-Fen; He, Shun-Zhi (Phytotaxa, 2014)
An unknown species of Aspidistra Ker-Gawler (1822: 628) with freshly opened flowers and full ripe fruits was found when the writer was doing field study at Guiding country, Guizhou province in October, 2008. This species bloomed again in October, 2011 after being introduced to Guiyang College of Traditional Chinese Medicine, then was identified as a new species after studying relevant literature (Fang & Yu 2002, He 2002, Li & Tang 2002, Li & Wei 2003, Li 2004, Tillich 2005, 2006, Tillich et al. 2007, Tillich & Averyanov 2008, Lin et al. 2009, 2011, 2014, Hou et al. 2009, Xu et al. 2010a, 2010b, He et al. 2011a, 2011b, 2013, Gao et al. 2011, Hu et al. 2014, Vislobokov et al. 2014a, 2014b, Meng et al. 2014).